2012
DOI: 10.1007/s00402-012-1576-6
|View full text |Cite
|
Sign up to set email alerts
|

6-Year follow-up of ventral monosegmental spondylodesis of incomplete burst fractures of the thoracolumbar spine using three cortical iliac crest bone grafts

Abstract: High rates of osseous consolidation are visible 6 years after ventral spondylodesis by iliac crest bone grafts. A further improvement of consolidation can be expected after dorsal implant removal. But the surgical approach to the iliac crest is accompanied with a relevant complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…Three patients complained about pain or hyposensitivity at 12 year follow-up. At 6-year follow-up, 71% of all patients were suffering from donor site pain [21]. These findings are consistent with the findings of Wippermann et al [22] who reported an overall complication rate of 19.6% after iliac crest harvesting.…”
Section: Clinical Outcomesupporting
confidence: 90%
“…Three patients complained about pain or hyposensitivity at 12 year follow-up. At 6-year follow-up, 71% of all patients were suffering from donor site pain [21]. These findings are consistent with the findings of Wippermann et al [22] who reported an overall complication rate of 19.6% after iliac crest harvesting.…”
Section: Clinical Outcomesupporting
confidence: 90%
“…In addition to this, the surgical approach to the iliac crest is associated with relevant morbidity including persisting long-term graft donor site pain [25]. The six-year outcomes of our patients, who were treated with an iliac crest bone graft, has been published recently [22]. The proportion of our patients suffering from donor site pain is high (71 %).…”
Section: Discussionmentioning
confidence: 96%
“…The other three patients suffered from minor discomfort. Only four patients (29 %) who were treated ventrally with an iliac crest bone graft did not mention any discomfort related to the donor site [22]. Eight of them (57 %) reported slight intermittent pain without any need of analgesics, whereas two patients (14 %), irregularly taking non-steroidal anti-inflammatory drugs, suffered persistent pain.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies on monosegmental anterior column reconstruction are scarce. Spiegl et al [27] assessed the clinical and radiological outcome of 14 patients with incomplete burst fractures after a mean of 74 months (range 66–84 months) after thoracoscopic monosegmental ACR using a tricortical iliac crest bone autograft and an additional ventral plate. Nine patients were treated by an anterior only approach and five patients were treated by a combined posterior–anterior approach.…”
Section: Discussionmentioning
confidence: 99%